The retrospective analysis results of the endometrial tissue pathological conditions development - V. V. Artyomenko; Z. V. Chumak; M. V. Shapoval (Publishing House TRILIST, 2020)
Hyperplastic processes of endometrium are one of the most common pathologies of the uterus mucosa, an interest in its study is due to an increase in the frequency of occurrence, the ability to both self-healing and malignancy. Purpose of the study: to investigate the detection rate of endometrial proliferative changes  depending on the age of woman. Materials and methods. A retrospective medical documentation analysis of the Department of Pathology was conducted. 2196 pathologic findings of endometrial tissue samples were investigated. 1404 specimen were hyperplastic states, 688 were endometrial polyps, and 104 others were endometrial states after total or subtotal uterine removal after surgery. Histological conditions were distributed according to patients' age categories. Results of the study were processed statistically using variation statistics with Student's criterion, using standard computer systems. Results. The analysis shows an increase in frequency of endometrial proliferative changes in perimenopausal patients on the background of endometrial pathological changes detection in all age categories. Atypical forms of simple and complex hyperplasia of the endometrium can be traced in all age categories, with a maximum frequency of manifestation in similar age-related periods - 41-45 years and 46-50 years. Morphological signs of endometrial tissue malignancy were first established in the age group of 46-50 years, which coincides with the age of the onset of menopause in the Odesa region, with subsequent relative increase in the frequency and aggressiveness of the process with age. These age groups focus doctors to be more careful about pathological manifestations. Conclusion. As a result of retrospective analysis of histopathological examinations it was found that the main factor in detecting pathological conditions of the endometrium is a woman's age of perimenopausal period, which can be considered as an early marker of diagnosis, leading to treatment prospects and general therapeutic tactics, for the future diagnostics and detection of others immunohistochemical and molecular genetic markers in women with hyperplastic processes in endometrial tissue.